Suicide of a Superpower: By Patrick J. Buchanan (New York: St. Martin’s Press, 2011. 488 pages.) (American Journal of Islam and Society, 2013)
Both a book of lamentation about the presumably collapsing American wayof life and a populist right-wing anti-establishment agenda of ethno-nationalistxenophobia, euphemistically referred to as “ethno-pluralism,” author PatrickBuchanan presents an alarmist message of doom and gloom about the fate ofhis country. He adopts this “master frame,” which allows him and the currenthe represents to mobilize anti-immigrant sentiments as well as politicalprotest in ways that limit vulnerabilities to accusations of racism or of beingantidemocratic (Rydgren 2004).1Buchanan starts his book by asserting that this generation of Americansis witnessing “one of the most stunning declines of a great power in the historyof the world” (p. 10). His thesis is that “America is disintegrating” and thatthe “centrifugal forces pulling [it] apart are growing inexorably. What onceunited us is dissolving. And this is true of Western civilization” (p. 7; my emphasis).The explanation he offers for this is framed within the context of theUnited States losing its Christian character, implying that non-Christians donot belong there; the breakdown of society’s moral, cultural, and social fabric,read as opposition to multiculturalism as well as to liberal values and policies;and the dying of the people who created this nation, which is now being overwhelmedby a rapidly increasing flow of immigrants and members of otherraces and ethnicities. Having rung the alarm, whether true or false, Buchananproceeds in the following eleven chapters to make his case, addressing sensitiveissues of religion, race and ethnicity, demography, multiculturalism, expansivegovernment, values of equality, and foreign relations – all of whichhe has something to say about in what appears to be some kind of an ideologicaltract ...